2018
DOI: 10.1111/ggi.13580
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in 1‐year mortality risks in older patients experiencing a first acute heart failure hospitalization

Abstract: Aim To assess whether 1‐year mortality in older patients experiencing a first admission for acute heart failure was related to sex, and to explore differential characteristics according to sex. Methods We reviewed the medical records of 1132 patients aged >70 years of age admitted within a 3‐year period because of a first episode of acute heart failure. We analyzed sex differences. Mortality was assessed using multivariate Cox analysis. Results There were 648 (57.2%) women (mean age 82.1 years) and 484 men (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The flow diagram of the study selection process is shown in Figure 1 . We identified 27 studies included in this meta-analysis that reported 30-day and 1-year readmission data and mortality after HF, 18–28 , 32–47 including 1 trial conducted in Japan, 18 12 in the US, 19 , 21 , 23–25 , 27 , 33 , 34 , 36 , 38 , 44 , 47 1 in Italy, 20 2 in Spain, 22 , 39 1 in India, 40 1 in Singapore, 41 1 in Romania, 42 1 in France, 26 1 in Australia, 28 1 in Switzerland, 32 1 in Korea, 35 1 in Argentina, 37 1 in South Africa, 43 1 in Europe 45 and 1 in England. 46 The total number of participants was 515,238.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The flow diagram of the study selection process is shown in Figure 1 . We identified 27 studies included in this meta-analysis that reported 30-day and 1-year readmission data and mortality after HF, 18–28 , 32–47 including 1 trial conducted in Japan, 18 12 in the US, 19 , 21 , 23–25 , 27 , 33 , 34 , 36 , 38 , 44 , 47 1 in Italy, 20 2 in Spain, 22 , 39 1 in India, 40 1 in Singapore, 41 1 in Romania, 42 1 in France, 26 1 in Australia, 28 1 in Switzerland, 32 1 in Korea, 35 1 in Argentina, 37 1 in South Africa, 43 1 in Europe 45 and 1 in England. 46 The total number of participants was 515,238.…”
Section: Resultsmentioning
confidence: 99%
“…43 Most of the articles reported similar data for 1-year all-cause mortality, ie, 29%. 32,34,36,[38][39][40]43,[45][46][47] The careful management of HF outpatients who are elderly, high disease severity, multiple comorbidities, or taking beta-blockers, loop diuretics, thiazide, or nitrates when discharged from the hospital may be critical to reducing the 30-day readmission. 18 In some studies assessed in this meta-analysis, the authors identified multiple predictive factors of readmission, including age 18,20,21 and clinical comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…shortness of breath and fatigue) that impair quality of life 3 and is also associated with high mortality rates, recurrent hospitalizations, and high direct and indirect costs. [4][5][6] Cognitive impairment (CI) is a common co-morbid condition in patients with HF. 7 Several studies have shown that CI in HF ranges between 20% and 80%, 7,8 and that CI is associated with poor HF outcomes, such as death, hospital readmission, and poor self-care.…”
Section: Introductionmentioning
confidence: 99%
“…HF is associated with several symptoms (e.g. shortness of breath and fatigue) that impair quality of life and is also associated with high mortality rates, recurrent hospitalizations, and high direct and indirect costs …”
Section: Introductionmentioning
confidence: 99%